Behavioral Economics and Its Applications - Vartiainen, Hannu; Diamond, Peter A. (Book collections on Project MUSE., 2007)
In the last decade, behavioral economics, borrowing from psychology and sociology to explain decisions inconsistent with traditional economics, has revolutionized the way economists view the world. But despite this general success, behavioral thinking has fundamentally transformed only one field of applied economics-finance. Peter Diamond and Hannu Vartiainen's Behavioral Economics and Its Applications argues that behavioral economics can have a similar impact in other fields of economics. In this volume, some of the world's leading thinkers in behavioral economics and general economic theory.